Pemanfaatan Google Site Sebagai Media Pembelajaran Siswa Pada SMKN 3 Kota Bengkulu - Eko Suryana; Prahasti Prahasti; Agung Pradana Iskandar (Universitas Dehasen Bengkulu, 2023)
Google Sites is a personal or professional website service that doesn't charge anything or is free. This service is a service created by the Google company. users can take advantage of Google Sites because they are easy to create and maintain for novice users. There are a number of uses that are owned by Google Sites that can be utilized by internet users. One of them is for learning. Google Sites can be utilized by teaching staff, such as teachers and lecturers who don't have time to provide online learning systems. Google Sites is a popular site builder tool because it has a number of advantages. First, this tool is free or free. secondly, the process of creating a site using Google Sites is very easy to build. third, these tools allow users to collaborate in their use. fourth, this tool provides 100 MB of free online storage. Fifth, easy to search using the Google search engine. The digital portfolio can be used to document the achievements that have been obtained from the journey during the service period, as well as a means to record personal development.